Dari Water Justice ke Water Ethics: Pendekatan terhadap Krisis Air Perspektif Egalitarianisme Kosmik dan Rasionalitas Kolektif Spinoza : From Water Justice to Water Ethics: Approaches to the Water Crisis: Cosmic Egalitarianism and Spinoza's Collective Rationality - Petrus Tan; Norbertus Jegalus; Siprianus S. Senda (Jurnal Filsafat Indonesia, 2026)
Water scarcity has influenced economic, social, cultural, and behavioral development, making it a global concern. This study approaches the crisis not merely as a technical or politico-economic issue as emphasized in previous water justice studies but as an ethical problem. Drawing on Spinoza’s metaphysics of biospheric egalitarianism and collective rationality, it develops the concept of water ethics, which regards water as an entity possessing intrinsic value and the right to exist. Using the interpretivist philosophical method, the study finds that all entities, including water, are modifications of a single substance endowed with conatus—the drive to preserve existence and relate to others on egalitarian terms. From this perspective, the study proposes three fundamental dimensions of water ethics: eco-justice, water rights, and water democracy, forming the basis for a new paradigm that guides humanity toward an ethics of coexistence within the biosphere. It concludes that addressing the water crisis requires a paradigmatic shift from the distributive justice framework of water justice to an ethical awareness of the existence and rights of non-human entities within water ethics.